Identification and Validation of Quantitative Trait Loci for Wheat Dwarf Virus Resistance in Wheat (Triticum spp.) - Pfrieme, Anne-Kathrin; Ruckwied, Britta; Habekuß, Antje; Will, Torsten; Stahl, Andreas; Pillen, Klaus; Ordon, Frank (Frontiers in Plant Science, 2022)
Wheat dwarf virus (WDV) is transmitted by the leafhopper Psammotettix alienus. As a major pathogen in wheat and other cereals, WDV causes high yield losses in many European countries. Due to climate change, insect-transmitted viruses will become more important and restrictions in the use of insecticides efficient against P. alienus renders growing of WDV resistant/tolerant varieties the only effective strategy to control WDV. So far there is little information about possible sources of resistance and no known information about genome regions responsible for resistance. In a screening for WDV resistance/tolerance using artificial inoculation in gauze houses, a panel of 500 wheat accessions including cultivars, gene bank accessions and wild relatives of wheat was phenotyped for virus titer, infection rate, as well as plant height and yield parameters relative to healthy controls of the same genotype. Additionally, 85 T. aestivum-Ae. tauschii intogression lines were tested for WDV resistance in the greenhouse. A subset of 250 hexaploid wheat accessions was genotyped with the 15 k iSelect SNP Chip. By genome-wide association study (GWAS) quantitative trait loci (QTL) for partial WDV resistance were identified. Within these studies, one cultivar was identified showing an average infection rate of only 5.7 %. By analysing single seed descent (SSD) and doubled haploid (DH) populations comprising 153 and 314 individuals for WDV tolerance and by genotyping these with the 25 K iSelect SNP Chip, QTL for yield per plant, thousand grain weight and relative virus titer were validated on chromosomes 1B, 2B, 3B, 4B, 4A, 5A, 6A and 7A. These results will be the basis for marker-assisted selection for WDV tolerance to replace the laborious, time-consuming and technically challenging phenotyping with WDV bearing leafhoppers.